First successful pregnancy in a globozoospermic patient having homozygous mutation in SPATA16 - (:unkn) unknown (ELSEVIER SCIENCE INC, 2014)
Objective: To report the first case of a successful pregnancy obtained with an infertile 29-year-old man with a homozygous mutation in the spermatogenesis-specific gene SPATA16 after intracytoplasmic sperm injection (ICSI). Design: Case report. Setting: Assisted reproductive technology (ART) center. Patient(s): A couple who suffered from infertility of whom the husband was globozoospermic and carrying a homozygous mutation in the spermatogenesis-specific gene SPATA16. Intervention(s): Clinical and histopathological evaluation, transmission electron microscopy, stimulation with fixed antagonist protocol, ICSI, activation of fertilization. Main Outcome Measure(s): In vitro fertilization and pregnancy. Result(s): Oligoasthenoteratozoospermia was revealed in semen analysis. Total globozoospermia was detected. Chromatin condensation pattern was detected abnormal in 88% of spermatozoa with aniline blue staining. During the ART cycle 12 oocytes were collected. Eleven oocytes were at the metaphase II and one was at the germinal vesicle stage. After the injection, one oocyte fertilized on the following day; the 4-cell stage embryo was transferred. Pregnancy occurred and a healthy boy was delivered after 42 weeks of gestation. Conclusion(s): This is the first report of a pregnancy obtained in a man with homozygous SPATA16 mutated globozoospermia. (C) 2014 by American Society for Reproductive Medicine.
Keywords: Globozoospermia; SPATA16 gene mutation; intracytoplasmic sperm injection; ASSISTED OOCYTE ACTIVATION; INTRACYTOPLASMIC SPERM INJECTION; ROUND-HEADED SPERMATOZOA; PHOSPHOLIPASE-C ZETA; CHROMATIN STRUCTURE; DPY19L2 DELETION; FERTILIZATION; INFERTILITY; MICROINJECTION; DELIVERY